Industrial megaprojects : concepts, strategies, and practices for success - Merrow, Edward W. (Hoboke, N.J. : Wiley, 2011)
"Avoid common pitfalls in large-scale projects using these smart strategies Over half of large-scale engineering and construction projects off-shore oil platforms, chemical plants, metals processing, dams, and similar projects have miserably poor results. These include billions of dollars in overruns, long delays in design and construction, and poor operability once finally completed. Industrial Megaprojects gives you a clear, nontechnical understanding of why these major projects get into trouble, and how your company can prevent hazardous and costly errors when undertaking such large technical and management challenges. Clearly explains the underlying causes of over-budget, delayed, and unsafe megaprojects Examines effects of poor project management, destructive team behaviors, weak accountability systems, short-term focus, and lack of investment in technical expertise Author is the CEO of the leading consulting firm for evaluating billion-dollar projects Companies worldwide are rethinking their large-scale projects following the BP's disastrous Gulf oil spill. Industrial Megaprojects is your essential guide for this rethink, offering the tools and principles that are the true foundation of safe, cost-effective, successful megaprojects."--
Includes index.
Keywords: Project management